9.0k views
4 votes
Given: f(x) = x - 7 and h(x) = 2x + 3

Write the rule for h(f(x)). h(f(x)) = 2x - 11 h(f(x)) = 2x - 7 h(f(x)) = 2x - 4 h(f(x)) = 3x - 4

2 Answers

3 votes

Answer:

h(f(x)) = 2x - 11


(the second answer is f(h(x)) = 2x - 4)

Explanation:

h(x-7) = 2(x-7) + 3

h(x) = 2x -14 + 3

h(x) = 2x - 11

User MattK
by
5.9k points
5 votes

Answer:

The correct answer option is h(f(x)) = 2x - 11

Explanation:

We are given two functions:


f(x) = x-7 and
h(x) = 2x+3

and we supposed to find another function which is
h(f(x)).

To find
h(f(x)), we need to substitute the value of
f(x) in the other function i.e.
h(x) to get:


h(f(x)) = h(x-7)


h(f(x))= 2(x-7)+3


h(f(x))=2x-14+3


h(f(x)) 2x-11

Therefore, the correct answer is h(f(x)) = 2x - 11.

User Mubir
by
6.4k points